THE DYNAMICS OF SOCIAL ECONOMIC LAW: A THEORETICAL AND PRACTICAL EVALUATION THROUGH LITERATURE REVIEW - Loso Judijanto; Rita Hayati (ADISAM Publisher, 2024)
Social economic law is a branch of law that regulates the relationship and interaction between economic and social aspects of society. It focuses on policies and regulations that aim to achieve a balance between economic growth and social justice, as well as ensuring the protection of vulnerable groups and the reduction of economic inequality. The results of this study show that despite the challenges, well-implemented social economy law can be an effective tool to achieve a more just and prosperous society with adaptive and inclusive strategies.